Control of anemia and transfusion in perioperative management of patients with hip fracture. A Cohort Study - Sanz Pérez, Marta Isabel; Guijarro Valtueña, Ainhoa; Hormaechea Bolardo, Lucía; Del Valle Quintans, Sara; Álvarez Bartolomé, Ana; del Campo Mur, Alejandra (Revista Colombiana de Ortopedia y Traumatología, 2021)
Background: Aim of the study is to describe the elements associated with hip fractures about needs for transfusion of blood products and their risk factors, as well as their modification through preoperative treatment through the administration of intravenous iron. Material and methods: A Cohort study of 119 patients admitted for hip fracture was conducted. Detailed description of the protocol for the pre-surgical optimization of these patients, epidemiological data, analytical values, as well as data on intravenous iron administration and need for transfusion were collected. Results: 31.09% of the patients were using platelet aggregation inhibitors and 21.85% were were using anticoagulants at the time of admission. The mean hemoglobin on admission was 12.5 g / dl. 43.2% were transfused during the hospital stay. In the analysis of risk factors for transfusion, we statistically demonstrated that both hemoglobin on admission (p < 0.001), as well as previous diagnoses of chronic anemia, arterial hypertension, and renal failure, are related to the need for intra-hospital transfusion. We found a statistically significant relationship between iron administration and the amount of packed red blood cells transfused (p < 0.005). Blood transfusion requirements were higher in extra-capsular than in intra-capsular fractures (p = 0.024). Discussion: Patients with hip fracture frequently present low hemoglobin levels upon admission, as well as comorbidities and treatments that predispose to the development of perioperative anemia. Preoperative optimization of these patients by administering intravenous iron could reduce transfusion requirements. Evidence Level: II